THE INFLUENCE OF THE DRILL METHOD ON APPLYING INFUSION SKILLS IN STUDENTS - Helsy Desvitasari; M. Ramadhani Firmansyah (Suluh Adiluhung Publisher (SAPub), 2024)
UNESCO (United Nations, Educational, Scientific and Cultural Organization) designed four pillars of education for both the present and the future, namely: (1) Learning to know, (2) Learning to do, (3) Learning to be, (4) Learning to live together. One way to achieve this pillar is by applying drill learning method in basic human nursing subjects at STIK Siti Khadijah Palembang. Through the training mechanism, students' knowledge and skills are increasingly honed. The aim of the research was to determine the influence of the drill method on the skills of applying IV fluids in STIK Siti Khadijah Palembang students. This research is classroom action research. The sample in this research were 65 first semester students of the STIK Siti Khadijah Palembang nursing science study program, taken as a total sampling. The analytical method used is quasi-experimental. The research results show that there is an influence of drill method on student skills with a p value <0.001. Through the drill method, students can practice honing their skills.